(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s ((3eMeO Hf YHO GdbGOQ GdMfajs)
(3ChdgG (B:s
(3CNHQfG CHh YeQ YHO GdhGMO Hf eMeO (B... (3EPG CJi CMOce Cgdg Ke GQGO Cf jYhO adjJhVC(B...s
(3BNQgG (B:s
(3CNHQfG YHO GdhGMO bGd MOKfG GdMSjf bGd MOKfG YHO Gddg(B... (3GdYeQI SfI dG JJQc hdjSJ HhGLHIs
(3QhGjI CHj YeQ YHO GdhGMO Hf eMeO Hf YHO Gddg Hf egOj GdaGQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs